IN SILICO COMPARATIVE ANALYSIS OF GENE AND PROTEIN OF PLANT LECTINS - Khairiya, Fathiya
Lectins are protein that have ability to recognize and bind to specific carbohydrates. Plant lectins have roles as plant defense, insecticidal agents, antibacterial, antifungal, and antiviral. Understanding of the characterization and comparison of genes and protein lectins from various plant species is important for further development of this protein. From this study, could get the information about the gene characteristics, domains and carbohydrate binding motifs. In the future, this information could be used to utilize lectin sequence as the biological parts for the coding sequence so that lectin proteins can be synthesized and further applied in the agriculture, health, and pharmaceuticals. Therefore, the aim of this study is to compare genes, proteins and carbohydrate binding motifs on 15 plant lectins using in silico method. The lectin gene from Artocarpus hypargyreus Hance, Hordeum vulgare var. Betzes, Triticum aestivum L. cv. Marshall, Galanthus nivalis L., Allium sativum L., Phaseolus vulgaris, Lens culinaris subsp. tomentosus, Robinia pseudoacacia, Glycine max, Cicer arietinum, Pisum sativum, Canavalia ensiformis, Amaranthus caudatus, and Amaranthus hypochondriacus were obtained from NCBI and Musa acuminata subs. Malaccensis was obtained from Banana Genome Hub, then BLASTX was performed on the same platform. The FGENESH+ and GeneWise programs were used to predict the gene structures of 15 plant lectins. For protein comparison, the motifs and domains were identified using MEME-Suite, CD-Search Tool, and validation with InterPro, then multiple sequence alignment was performed using MUSCLE method to compare the carbohydrate binding motifs in each species compared to the consensus motifs from literatures. The construction of phylogenetic tree was carried out using the Maximum Likelihood method with MEGA-X. The gene comparison shows that the lectin genes in 15 plant species have different characteristics with the shortest gene from Artocarpus hypargyreus and the longest gene from Glycine max, and 15 plant lectin genes have 1 to 3 exons. The prediction of domains result in 5 domains, named Jacalin, Chitin_bind_1, B_lectin, Legume lectin and Agglutinin. Furthermore, there are 2 protein sequences from Jacalin domain, 2 protein sequences from Chitin_bind_I domain, 2 protein sequences from B_lectin domain, and 4 protein sequences from Legume lectin domain that have complete carbohydrate binding motifs compared to consensus motifs from literatures.